Development of Project Based Learning E-Modules on Android Based Embedded System Subjects - Abdul Habib Arrasyidi Desky; Taali; Hansi Effendi; Hasan Maksum (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an e-module based on Project Based Learning (PjBL) for the subject of Embedded Systems that can be accessed via Android devices. The development of this e-module is motivated by the need for interactive, contextual, and project-based learning materials, particularly to enhance students' competencies in Industrial Electronics Engineering that are valid, practical, and effective for the Embedded Systems subject in Grade X Industrial Electronics Engineering at SMKN 1 Sumbar. The development of this e-module is intended to enhance students' understanding, motivation, and independent learning, thereby improving their learning outcomes. The research method used is Research and Development (R&D), employing the 4D development model (define, design, develop, and disseminate). Primary data in this study were obtained from validators, teachers, and students. The data were analysed descriptively to determine the validity, practicality, and effectiveness of the developed learning media. The validity test results showed that this learning media, with a media aspect score of 0.895 and a material aspect score of 0.960, was deemed valid by experts. The media was also deemed practical, with a practicality score of 98.94% from teacher responses and 95.25% from student responses. In the effectiveness test, the Gain Score obtained was 0.69, placing it in the moderate category. Meanwhile, the t-test showed a Sig value (2-tailed) of 0.002 (2-tailed < 0.05) and a t-count value of 3.375 (t-count > t-table), indicating a significant difference in learning outcomes between students using this learning media (experimental class) and those not using it (control class). Thus, this PjBL-based e-module can be used as an interactive teaching material alternative that is suitable for 21 st-century learning needs and is valid, practical, and effective.